Foot massage among diabetes patients: A concept analysis using Walker and Avant’s method - Cruz, Maria Kristina Dela; Manuel, Jose Reyes; Chiyapan, Anurak (Lentera Perawat, 2025)
Background Foot massage is increasingly used as a complementary therapy in diabetes care, particularly for patients suffering from diabetic peripheral neuropathy. Despite its widespread use, the concept remains theoretically underdeveloped, inconsistently defined, and variably applied in nursing practice. Objective This study aimed to clarify the concept of foot massage among diabetes patients through a structured concept analysis using Walker and Avant’s eight-step method. Methods A concept analysis was conducted following the Walker and Avant framework. Literature was reviewed from databases including PubMed, Scopus, CINAHL, and Google Scholar using keywords related to foot massage, diabetes, and non-pharmacological interventions. The defining attributes, antecedents, consequences, model cases, and empirical referents of the concept were identified and analyzed. Results Five defining attributes emerged: (1) manual stimulation of the feet, (2) therapeutic intention, (3) relief of physical and psychological symptoms, (4) enhancement of circulation, and (5) facilitation of self-care awareness. Antecedents included the presence of diabetic neuropathy and patient willingness to engage in complementary care. Consequences ranged from pain reduction and improved circulation to increased self-care adherence. Empirical referents included pain scores, circulation metrics, and patient-reported outcomes. Conclusion Foot massage among diabetes patients is a multidimensional therapeutic concept that holds significant value in holistic nursing care. This analysis provides a theoretical foundation for its application in practice, research, and nursing education, emphasizing its potential to enhance comfort, self-management, and quality of life in diabetic care.